Looking for Group: Sociality, Embodiment, and Institutions in World of Warcraft - (:unkn) unknown (My University, 2019)
This ethnography examines the varying degrees of conflict between multiple stakeholders involved in the massively multiplayer online role-playing game World of Warcraft (WoW). The game’s designers, like many software developers in the contemporary world, tend to be guided by an ideology influenced by classical liberalism, but also inspired by a utopian view of technology in general. That ideological position has directly affected many aspects of the game, from the largely unregulated in-game economy, to the strong emphasis on individual mastery of the game’s systems to progress through the complete content of the game world. World of Warcraft advertises itself not just on its narrative and combat mechanics; it also entices players to participate because of its very nature as a multiplayer game. The structure of WoW encourages players to join together in tight-knit communities (“guilds”) not just to overcome powerful opponents, but to socialize as well. In this way the game exists for many players as a significant social outlet in their everyday lives. However, players, guilds, and designers exist in a state of tension due to the ideological and architected constraints of the game. Due to the classical liberal bent of WoW promoting individual achievement through the game’s many obstacles, players oftentimes find themselves having to break away from close friends they game with in order to follow the primary goals of the narrative. This leads to an environment where players are constantly weighing the social bonds they establish and/or maintain through play against the concerns of software programmers intent on directing them to endgame content above all else.
Keywords: Embodiment; Games; Institutions; Sociality; Warcraft